Acute and chronic nicotine effects on behaviour and brain activation during intertemporal decision making. (16th May 2013) - Kobiella, Andrea; Ripke, Stephan; Kroemer, Nils B.; Vollmert, Christian; Vollstädt‐Klein, Sabine; Ulshöfer, Dorothea E.; Smolka, Michael N.
Abstract Previous studies demonstrated higher discount rates for delayed rewards in smokers than non‐smokers. We performed this study to determine whether those differences in intertemporal choice are due to pharmacological effects of nicotine and to track related brain regions. Thirty‐three non‐smokers and 27 nicotine‐dependent smokers underwent functional magnetic resonance imaging while performing an intertemporal choice task consisting of 40 sets of monetary reward options that varied by delay to delivery. Smokers were investigated in a state of nicotine satiation. Non‐smokers were investigated twice, receiving nicotine (2 mg) and placebo gums in a double‐blinded, randomized cross‐over design. Smokers displayed steeper temporal discounting than non‐smokers. Those behavioural differences were reflected in the brain response during the decision between two alternative money/time pairs: smokers showed less activation in parietal and occipital areas (e.g. precuneus) than non‐smokers under placebo. A single dose of nicotine in non‐smokers led to a similar effect on brain activation but did not impact behaviour. Processing of the reward magnitude of money/time pairs differed between smokers and non‐smokers: smokers showed decreased reactivity of the ventral striatum. Moreover, there was an acute nicotine effect in non‐smokers on processing of the reward magnitude: nicotine increased the correlation of blood oxygen level‐dependent response and mean amount in the left hippocampus, amygdala and anterior insula. We conclude that cross‐sectional differences between smokers and non‐smokers are only, in part, due to the acute pharmacological effects of nicotine. Longitudinal studies are needed to investigate pre‐drug group characteristics as well as consequences of smoking on discounting behaviour and its neural correlates.